2022
DOI: 10.3390/ma15093245
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Penetration Characterization of Colored Boundaries in Powder-Based Color 3D Printing

Abstract: Color 3D printing has widely affected our daily lives; therefore, its precise control is essential for aesthetics and performance. In this study, four unique test plates were printed using powder-based full-color 3D printing as an example; moreover, the corresponding pigment-penetration depth, chromaticity value and image-based metrics were measured to investigate the lateral pigment penetration characteristics and relative surface-color reproduction of each color patch, and to perform an objective analysis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…3.1 3D printed structural color patterns 3D printing is an additive manufacturing technology, where 3D models are sliced by software and then printed out layer by layer through a printer to realize the model in three dimensions. Especially in recent decades, 3D printing technology has developed rapidly, from single color printing to color printing (Yao et al, 2022); printing principles such as SLA, FDM, SLS and other technologies are also varied.…”
Section: Resultsmentioning
confidence: 99%
“…3.1 3D printed structural color patterns 3D printing is an additive manufacturing technology, where 3D models are sliced by software and then printed out layer by layer through a printer to realize the model in three dimensions. Especially in recent decades, 3D printing technology has developed rapidly, from single color printing to color printing (Yao et al, 2022); printing principles such as SLA, FDM, SLS and other technologies are also varied.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some preliminary studies have also confirmed that chromatic metrics do not precisely match human vision in terms of color representation for color 3D printed objects, and more evaluation metrics are needed [ 19 , 20 ]. For this reason, image-based metrics have been gradually developed for color 3D printing, such as structural similarity, feature similarity, and image difference, which are full-reference image quality comparison metrics [ 21 , 22 , 23 ]. These image-based metrics are implemented in statistics, from grayscale map comparison to color map comparison.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 So, it is needed to determine the boundary coloring width of each slice. 18 The color definition of the internal voxels within a certain range under the surface of the color 3D model is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to a general 3D printing system which only needs to define the number and thickness of slices, a multi‐jet system machine using translucent materials for color 3D models also relies on the accurate definition of color of the voxels under the surface of the material for better visual effects 16,17 . So, it is needed to determine the boundary coloring width of each slice 18 . The color definition of the internal voxels within a certain range under the surface of the color 3D model is very important.…”
Section: Introductionmentioning
confidence: 99%